A Review on the Antibacterial Activity of Edible Mushrooms - Maha, Noor; Lalita Ambigai, Sivasamugham; Geetha, Subramaniam (INTI International University, 2021)
Edible mushrooms produce a variety of bioactive compounds that could be used as alternatives to antibiotics. This review was aimed to evaluate the antibacterial activities of most common edible mushrooms. Extracts of oyster, button, shiitake and enokitake mushrooms showed inhibition against various gram-negative and gram-positive bacteria with the latter being more susceptible towards the mushroom extracts. The zones of inhibition differed in the disk diffusion assay and the agar well diffusion assay as it was dependent on the type and the concentration of the extract used. Larger zones of inhibition were generally seen in the studies that used agar well diffusion assays as it used larger volumes of concentrated mushroom extracts. While many solvents were used to extract the bioactive compounds from these mushrooms, the ethanolic, methanolic and aqueous were the common extraction solvents used. The methanolic and ethanolic extracts also showed the highest zone of inhibition ranging from 8.3mm to 18.4mm indicating its effectiveness in extracting the bioactive compounds with antibacterial properties. Flavonoids, tannins, fatty acids, esters and lenthionine have been identified as some of the common chemicals in the mushroom extract that exhibit antibacterial effects on tested bacteria. However, further research on these compounds is required apart from the analysis on the possible combination of mushroom extracts which could exhibit synergistic antibacterial activities eventually suggesting the potential of the mushroom extracts as possible alternatives to antibiotics